Restless Legs Syndrome as the Presenting Symptom of Multiple Myeloma - Aricò, Debora (American Academy of Sleep Medicine, 2013)
We report a patient affected by restless legs syndrome as the presenting symptom of multiple myeloma, a hematologic malignancy characterized by clonal proliferation of plasma cells in the bone marrow and monoclonal immunoglobulin in the blood and/or urine. CITATION: Aricò D; Raggi A; Siragusa M; Zucconi M; Ferri R. Restless legs syndrome as the presenting symptom of multiple myeloma. J Clin Sleep Med 2013;9(4):383-385.